Concentration camps in Nazi Germany : the new histories - Caplan, Jane 1945- HerausgeberIn; Wachsmann, Nikolaus 1971- HerausgeberIn (Routledge, 2010)
The notorious concentration camp system was a central pillar of the Third Reich, supporting the Nazi war against political, racial and social outsiders whilst also intimidating the population at large. Established during the first months of the Nazi dictatorship in 1933, several million men, women and children of many nationalities had been incarcerated in the camps by the end of the Second World War. At least two million lost their lives. This comprehensive volume offers the first overview of the recent scholarship that has changed the way the camps are studied over the last two decades. Written by an international team of experts, the book covers such topics as the earliest camps; social life, work and personnel in the camps; the public face of the camps; issues of gender and commemoration; and the relationship between concentration camps and the Final Solution. The book provides a comprehensive introduction to the current historiography of the camps, highlighting the key conclusions that have been made, commenting on continuing areas of debate, and suggesting possible directions for future research.